SISTEM INFORMASI PENDISTRIBUSIAN DAN MONITORING PROGRAM KERJA KARYAWAN PADA NOIBLE BERBASIS WEB - Rafi Ramadhan (2024)
In the current era of globalization which has become so rapid. Technological developments in company digitalization are increasingly influencing internal and external progress. Information and communication greatly influence civilization, enabling work within a company to be completed quickly, accurately and efficiently, especially in businesses that are just starting out. Noible is a local brand that operates in the fashion sector, therefore, Noible needs progress in developing systems in its business. One thing that really influences the company's progress is the internal team, namely human resources, everyone who works in their field will have a big influence on the company's progress. In this system design analysis, PIECES analysis is used and the software development method uses the Waterfall method. Noible distributes and monitors employee work programs in the form of website-based applications using the PHP and MySQL programming languages as data storage in the database. The result of this research is the creation of a distribution and monitoring system for employee work programs. Keywords: Waterfall, Web, Employees, Monitor